2015
DOI: 10.1371/journal.ppat.1004768
|View full text |Cite
|
Sign up to set email alerts
|

Herpesviral G Protein-Coupled Receptors Activate NFAT to Induce Tumor Formation via Inhibiting the SERCA Calcium ATPase

Abstract: G protein-coupled receptors (GPCRs) constitute the largest family of proteins that transmit signal to regulate an array of fundamental biological processes. Viruses deploy diverse tactics to hijack and harness intracellular signaling events induced by GPCR. Herpesviruses encode multiple GPCR homologues that are implicated in viral pathogenesis. Cellular GPCRs are primarily regulated by their cognate ligands, while herpesviral GPCRs constitutively activate downstream signaling cascades, including the nuclear fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 76 publications
0
45
0
Order By: Relevance
“…Immunoprecipitation was carried out as previously described (Zhang et al, 2015a). Briefly, THP-1 cells were infected with HSV-1 FLAG-UL37 recombinant virus (MOI = 0.5) for 16 h. Cells were harvested and lysed with NP40 buffer (50 mM Tris-HCl [pH 7.4], 150 mM NaCl, 1% NP-40, 1 mM EDTA, 5% glycerol) supplemented with a protease inhibitor cocktail (Roche).…”
Section: Star Methodsmentioning
confidence: 99%
“…Immunoprecipitation was carried out as previously described (Zhang et al, 2015a). Briefly, THP-1 cells were infected with HSV-1 FLAG-UL37 recombinant virus (MOI = 0.5) for 16 h. Cells were harvested and lysed with NP40 buffer (50 mM Tris-HCl [pH 7.4], 150 mM NaCl, 1% NP-40, 1 mM EDTA, 5% glycerol) supplemented with a protease inhibitor cocktail (Roche).…”
Section: Star Methodsmentioning
confidence: 99%
“…Although being a homologue of human CXCR2, vGPCR induces a set of downstream signaling distinct from those of cellular chemokine receptors. While human chemokine receptors predominantly signal via Gα i proteins, vGPCR promiscuously couples to multiple Gα proteins and activates diverse downstream signaling cascades, such as phospholipase C (PLC) [22], NFAT [50, 51], MAPK [52, 53], PI3K-AKT [54] and Hippo-YAP [55]. Activation of phosophoinositide 3-kinase (PI3K) occurs largely through Gα i [54], while activation of YAP is dependent on Gα q/11 and Gα 12/13 [55].…”
Section: Kshv Vgpcrmentioning
confidence: 99%
“…However, it was shown that vGPCR can mobilize calcium release from the ER compartment via inhibiting the Sarco/Endoplasmic reticulum calcium ATPase (SERCA) [51]. The possible cooperation between Gα q and SERCA signaling warrants further investigation.…”
Section: Kshv Vgpcrmentioning
confidence: 99%
See 2 more Smart Citations